Patlau A Typical Food From Pontianak Culture in The Month of Ramadhan and Its Relevance to The Concept of Geometry of Spatial Figures - Mukmin, Chairul; Sarassanti, Yumi (THETA: Jurnal Pendidikan Matematika, 2024)
n Indonesia, there are many cultures from various regions, making it a diverse country. From culture, of course there are special foods from each region, so Indonesia is known as a country that has many regional specialties. The aim of this research is to observe the food found in various regions and also try to see its relationship to the concept of spatial geometry. This research method uses "descriptive research" meaning that we directly analyze the research objects that we will target, for example in various regions that have typical foods that are very popular in that area. We are required to provide descriptive research with the benefit of providing results from our analysis in the place where we conducted the research with an accurate discussion. The object that will be analyzed is the typical food of the month of Ramadan on the Eid al-Fitr holiday in the city of Pontianak, namely Patlau. The instruments used were observation and interviews and the data analysis technique used was descriptive analysis. It is hoped that with this research we can understand that learning mathematics is not only in the form of patterns wrapped in formulas that we know in mathematics, but that mathematics is broad in scope as we can relate it to existing cultures.